Interação entre a matéria orgânica natural, o cobre e microorganismos heterotróficos: implicações na dinâmica do metal e sua disponibilização para a biota aquática - Nogueira, Patrícia Franklin Mayrink (2007)
The increasing eutrophication and contamination of aquatic ecosystems motivates the study of interactions between natural dissolved organic matter (DOM), metals and the biota. Metals are mainly released into the environment by industrial processes, whereas organic materials through municipal sewage sludge. The association of these two processes and its effect on the environment poses unknown risks to aquatic communities. The support capacity of aquatic systems is related to its ability to associate with dissolved elements. In this study, the complexation capacity of Monjolinho Reservoir (eutrophic), from which the test organisms were obtained, was evaluated. The results showed that two copper-complexing sites were present, what contributes to the low free copper ion concentration in such environment. It is known that natural DOM is formed by humic like and recently produced organic compounds. Suwannee River natural organic matter was used throughout this investigation as models of humic substance DOM (commercial standard), whereas as model substance of recently produced organic material, cyanobacteria (Anabaena spiroides) exopolysaccharides were used. Considering that the environmental fate and chemical speciation of copper are dominated by natural DOM and that heterotrophic bacteria processes are responsible for nutrient regeneration, carbon transfer and energy, it was also investigated the influence of the interaction DOM-Cuorganisms on copper dynamic and bioavailability. The results showed that the natural bacteria population was copper resistant, tolerating up to 10-6 M total copper concentration. The degradation of DOM by heterotrophic bacteria, detected by fluorescence spectroscopy, revealed that after Cu-complexed DOM degradation, the metal was liberated into the environment, causing toxicity and bioaccumulation in the microbial food chain. Nevertheless, this was less pronounced when the organic materials were exopolysaccharides. In general, the results showed that copper complexed to natural DOM or exopolysaccharides was less toxic to the organisms than free copper ions. The present results are a contribution to aquatic ecosystems management and to the knowledge of copper speciation, availability and interaction with aquatic organisms, as it relates to dissolved organic materials in aquatic ecosystems.